Solemyidae (Bivalvia, Protobranchia) from the lower Miocene of south-central Chile, with description of a new species. (January 2020) - Pérez-Barría, Leonardo; Nielsen, Sven N.
Abstract: The Miocene Solemyidae of Chile are revised. The holotype of Solemya antarctica Philippi, 1887, originally described as Solenomya, is lost. Due to the lack of information on internal characters, its systematic position is considered as uncertain. A new species, Solemya lucifuga n. sp., is described from the lower Miocene Ranquil Formation of south-central Chile. Its dense radial external ornamentation shows that it is clearly different from S . antarctica . It is currently the only confirmed and described Miocene solemyid bivalve from the Southern Hemisphere. UUID: http://zoobank.org/a35ee02e-600b-4e9f-ad06-1887e9493ff8